PREVENTION AND PREVENTION OF HOUSEHOLD VIOLENCE IN UKRAINE UNDER THE CONDITIONS OF MARITAL STATE - Litvinova, Iryna; Linchuk, Bohdana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: by analyzing statistical data on the number of cases of domestic violence during the period of martial law, which are made public by subjects implementing measures in the field of prevention and counteraction of domestic violence, to consider the directions and effectiveness of state policy in the field of prevention and counteraction of domestic violence in Ukraine during military operations Research methods: the following methods were used: analysis method (processing of literary sources, court decisions, statistical research data); comparison (comparison of statistical data on the perpetration of domestic violence in 2022 and in previous years). Results: it was established that the activities of response bodies to cases of domestic violence and the administration of justice in cases of perpetration of domestic violence require established practice and specialized personnel training. It is suggested that in order to create an effective system for preventing and countering domestic violence, especially during the period of martial law, it is necessary to ensure the proper response of law enforcement agencies to cases of domestic violence and to bring perpetrators to justice. Discussion: the effectiveness of the exercise of powers by entities that carry out measures in the field of prevention and countermeasures against domestic violence in accordance with the provisions of normative legal acts that regulate the activities of such entities, especially in the context of military operations. The main changes that need to be carried out in the near future are the reform of private prosecution in cases of domestic violence to public prosecution, personnel training of persons (law enforcement officers, psychologists and others) who will specialize specifically in cases of violence, the creation of foreign bodies that will provide assistance to Ukrainian women , who left the borders of Ukraine, criminalization of such actions as harassment and mutilation of female genitals, making changes to the educational programs of schoolchildren to carry out preventive actions at the age when the attitude towards the surrounding world is being formed.